Additive value of nicorandil on ATP for further inducing hyperemia in patients with an intermediate coronary artery stenosis. Issue 2 (March 2017) - Kobayashi, Yuhei; Okura, Hiroyuki; Neishi, Yoji; Higa, Tomitaka; Kobayashi, Yukari; Uemura, Shiro; Yoshida, Kiyoshi
Abstract : Background: The induction of hyperemia is of importance to precisely assess the functional significance of coronary artery lesions with fractional flow reserve (FFR). Adenosine or ATP alone is used widely in this setting; however, little is known about the additive value of nicorandil, which acts as a nitrate and a K + -ATP channel opener, to induce further hyperemia. Patients and methods: A total of 183 intermediate native coronary artery lesions from 112 patients were prospectively enrolled into this study. FFR was measured using a coronary pressure wire during an intravenous ATP infusion alone (150 mcg/kg/min) (FFRATP ) and repeated after an adjunctive intracoronary nicorandil injection (2.0 mg) (FFRATP+Nico ). Results: Physiologic measurements were completed without any severe adverse effects from ATP and nicorandil in all patients. FFRATP and FFRATP+Nico had a strong linear correlation ( R 2 =0.79, P <0.001). The FFR value became significantly lower with an adjunctive intracoronary nicorandil injection compared with ATP alone [FFRATP vs. FFRATP+Nico, 0.87 (interquartile range: 0.81–0.92) vs. 0.85 (0.79–0.90), P <0.001]. A total of 18 lesions out of 183 (9.8%) were reclassified after a nicorandil injection (12 from FFR>0.80 to ⩽0.80 vs. six from FFR⩽0.80 to >0.80, P =0.26). The adjunctive effect of nicorandil was accentuated with each increment of FFRATP strata (per 0.05 increase, P for trend<0.001), but with minimal effect around the borderline FFR zone. Conclusion: An adjunctive intracoronary nicorandil injection is safe, but appears to have little effect in inducing further hyperemia. Therefore, its effect on the clinical scenario is limited.